2015
DOI: 10.1590/1807-1929/agriambi.v19n4p394-401
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial das frações da matéria orgânica do solo em área degradada sob recuperação

Abstract: R E S U M OObjetivou-se, neste estudo, avaliar a variabilidade espacial das frações da matéria orgânica do solo em uma área degradada em recuperação com pinhão-manso; para isto se estabeleceu, em um Argissolo Vermelho-Amarelo, uma malha de 30 por 30 m para amostragem, totalizando 55 pontos. Em cada ponto foram coletadas amostras de solo nas camadas de 0-0,05; 0,05-0,10 e 0,10-0,20 m e determinados carbono orgânico total (COT), carbono lábil (CL) e o carbono das frações ácido fúlvico (C-FAF), ácido húmico (C-FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
2
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
4
2
1
2
Order By: Relevance
“…The variables C-FAF, C-HUM, COp and COam at 20-40 cm depth presented strong spatial dependence, while the variables C-HAF, TOC, COp and COam (10-20 cm) and TOC (20-40 cm) showed moderate spatial correlation and the COam variable (0-10 cm) presented weak spatial dependence. Leite et al (2015) conducted a study evaluating the spatial variability of SOM fractions in a degraded area under recovery with Jatropha curcas L., in southwestern Piauí, and found different results of the present study. They adjusted the spherical model for the TOC and labile carbon (LC) variables in the 0-5 cm layer, for TOC, C-HAF and C-HUM variables in the 5-10 cm layer and for TOC in the 10-20 cm layer.…”
Section: Resultscontrasting
confidence: 74%
“…The variables C-FAF, C-HUM, COp and COam at 20-40 cm depth presented strong spatial dependence, while the variables C-HAF, TOC, COp and COam (10-20 cm) and TOC (20-40 cm) showed moderate spatial correlation and the COam variable (0-10 cm) presented weak spatial dependence. Leite et al (2015) conducted a study evaluating the spatial variability of SOM fractions in a degraded area under recovery with Jatropha curcas L., in southwestern Piauí, and found different results of the present study. They adjusted the spherical model for the TOC and labile carbon (LC) variables in the 0-5 cm layer, for TOC, C-HAF and C-HUM variables in the 5-10 cm layer and for TOC in the 10-20 cm layer.…”
Section: Resultscontrasting
confidence: 74%
“…Humic substances ( Figures 1D, 1E, and 1F) showed a nonuniform distribution pattern in the study area. The findings of the present study agree with the findings of Leite et al [26], who, analyzing the spatial variability of soil organic matter fractions in a degraded recovery area with Jatropha, in southwestern Piauí, Brazil, observed heterogeneous HS distribution.…”
Section: Resultssupporting
confidence: 93%
“…However, these stocks accounted for only 61 % of the stock in the natural soil. These data agree with those of Leite et al (2015), who found a low C content in the labile and non-labile OM of the 0.00-0.05 m layer of an Acrisol covered with Jatropha curcas for one year, after a long period of degradation by mining and uncontrolled burning and grazing. The HF is considered the OM density fraction with least sensitivity to changes in the soil management/crop systems, because aside from the biochemical recalcitrance of organic molecules and physical protection, the association of OM with soil minerals acts as a protection mechanism.…”
Section: Effect Of Cover Crops On Toc and Om Fractionssupporting
confidence: 92%